Insular and occipital changes in visual snow syndrome: a BOLD fMRI and MRS study. Issue 3 (10th March 2020) - Puledda, Francesca; Ffytche, Dominic; Lythgoe, David J.; O'Daly, Owen; Schankin, Christoph; Williams, Steven C. R.; Goadsby, Peter J.
Abstract: Objective: To investigate the pathophysiology of visual snow (VS), through a combined functional neuroimaging and magnetic resonance spectroscopy ( 1 H‐MRS) approach. Methods: We applied a functional MRI block‐design protocol studying the responses to a visual stimulation mimicking VS, in combination with 1 H‐MRS over the right lingual gyrus, in 24 patients with VS compared to an equal number of age‐ and gender‐matched healthy controls. Results: We found reduced BOLD responses to the visual stimulus with respect to baseline in VS patients compared to controls, in the left ( k = 291; P = 0.025; peak MNI coordinate [‐34 12 ‐6]) and right ( k = 100; P = 0.003; peak MNI coordinate [44 14 ‐2]) anterior insula. Our spectroscopy analysis revealed a significant increase in lactate concentrations in patients with respect to controls (0.66 ± 0.9 mmol/L vs. 0.07 ± 0.2 mmol/L; P < 0.001) in the right lingual gyrus. In this area, there was a significant negative correlation between lactate concentrations and BOLD responses to visual stimulation ( P = 0.004; r = −0.42), which was dependent on belonging to the patient group. Interpretation: As shown by our BOLD analysis, VS is characterized by a difference in bilateral insular responses to a visual stimulus mimicking VS itself, which could be due to disruptions within the salience network. Our results also suggest that patients with VS have a localized disturbance in extrastriate anaerobic metabolism, which may in turn cause a decreased metabolic reserve for the regular processing of visual stimuli.